Free versus total serum 25-hydroxyvitamin D in a murine model of colitis. Issue 189 (May 2019) - Larner, D.P.; Jenkinson, C.; Chun, R.F.; Westgate, C.S.J.; Adams, J.S.; Hewison, M.
Graphical abstract: Highlights: Mice fed vitamin D2 only from weaning showed lower total serum 25OHD than mice fed vitamin D3 at 8 weeks of age. Mice fed vitamin D2 only showed higher levels of free serum 25OHD than vitamin D3 mice. Mice fed vitamin D2 or vitamin D3 diets showed similar severity of colitis induced by dextran sodium sulphate. Free 25OHD may be more important than total 25OHD for anti-inflammatory responses. Abstract: Inflammatory bowel diseases (IBD) such as ulcerative colitis and Crohn's disease have been linked to vitamin D-deficiency. Using a dextran sodium sulphate (DSS)-induced model of IBD we have shown previously that mice raised on vitamin D-deficient diets from weaning have lower serum 25-hydroxyvitamin D (25OHD) levels and develop more severe colitis compared to vitamin D-sufficient counterparts. We have also shown in vitro that immune responses to 25OHD may depend on 'free' rather than total serum concentrations of 25OHD. To investigate the possible effects of free versus total 25OHD on anti-inflammatory immune responses in vivo we have studied DSS-induced colitis in wild type C57BL/6 mice raised from weaning on diets containing vitamin D2 (D2) or vitamin D3 (D3) only (both 1000 IU/kg feed). 25OHD2 has lower binding affinity for the vitamin D binding protein than 25OHD3 which results in higher levels of free 25OHD2 relative to free 25OHD3 in mice raised on a D2-only diet. Total serum 25OHD concentrations, measured by liquid chromatography-tandem mass spectrometry (LC–MS/MS), showed that D2 mice had significantly lower levels of 25OHD than D3 mice (6.85 ± 2.61 nmol/L vs . 49.16 ± 13.8 nmol/L for D2 and D3 respectively). Despite this, direct ELISA measurement showed no difference in free serum 25OHD levels between D2 and D3 mice (13.62 ± 2.26 pmol/L vs . 14.11 ± 2.24 pmol/L for D2 and D3 respectively). Analysis of DSS-induced colitis also showed no difference in weight loss or disease progression between D2 and D3 mice. These data indicate that despite D2-fed mice being vitamin D-deficient based on serum total 25OHD concentrations, these mice showed no evidence of increased inflammatory colitis disease relative to vitamin D-sufficient D3 mice. We therefore propose that free, rather than total serum 25OHD, may be a better marker of immune responses to vitamin D in vivo .